PERSISTENSI SKEWNESS RETURN POSITIF ANTAR PERIODA RETURN: SAHAM INDIVIDUAL DAN PORTOFOLIO (BURSA EFEK JAKARTA, 2001-2006) - Sumiyana Sumiyana (Faculty of Economics and Business, Universitas Gadjah Mada, 2007)
This research investigates stock returns to be consistently positively skewed. Thefrequency of positive skewness is found to be relatively stable over varying time periods.Controversially, in regards to others empirical research, past positively-skewed returns donot predict future positively-skewed returns. This research used daily and weekly data inJSX (Jakarta Stock Exchange). Samples of the data are the firms ever listed in LQ 45indexes for the year of 2001-2006.The positively-skewed returns of individual stocks are relatively rare (small proportion).Furthermore, the positively-skewed returns are likely occured incidentally only.Sequentially, this research conducted to control using 100 portfolios that composed withfive stocks and 20 stocks in each portfolio. Having controlled, this research concludedequivalent results with individual stock before. This research also suggests that pastpositively-skewed returns do not predict future positively-skewed returns. Finally, theskewness of individual stocks and portfolios does not persist across different periods. Thisresearch inffered that investors in JSX face uncertainty.Keywords: skewness persistence, consistently, mean (first-moment), variance (secondmoment), skewness (third-moment), random portfolios, distribution of stock returns, multiperiod case.